"Perturbed oral microbiome and their interaction as molecular signature in the early prognosis of oral cancer progression". (5th January 2023) - Muthukrishnan, Lakshmipathy
Highlights: Oral microbiome remains the most indispensable part of human microbiota. Their importance as potent biomarkers for several oral tumors is explored. Alteration in microbiome and the risk in carcinogenesis augment early detection. A wide array of bacteria is associated with different types of oral cancer. Mechanism of oral cancer progression by Porphyromonas sp. is highlighted.